An Inherent Decoupled Triple-Active Bridge Converter for All-Electric Aircraft DC Power Systems - Giuseppe Bossi; Nicola Campagna; Mauro Boi; Rosario Miceli; Alfonso Damiano (Energies)
This paper focuses on a power conditioning system for an all-electric aircraft (AEA) powered by a single battery pack. The research project aims to identify a multi-port DC/DC converter topology that adequately supplies the two DC buses connected to the propulsion system and auxiliary equipment, respectively. To achieve this, a triple-active bridge (TAB) in its inherently decoupled configuration has been investigated, prototyped, and experimentally verified. The TAB voltage control system was designed, simulated, and experimentally validated. Specifically, start-up, steady-state and step-load performances were evaluated by the simulation study and then experimentally validated on a scaled prototype. The results assess the feasibility of using an inherently decoupled TAB as a power conditioning system for interconnecting the AEA battery pack with the electric propulsion and auxiliary systems. In particular, the developed TAB configuration secures the decoupled power transfer between the two output ports providing at the same time good dynamic performance in terms of voltage control during step-load variation.